Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.12928/telkomnika.v18i5.13552
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcium carbonate and titania particles on improving color homogeneity and luminous flux of WLEDs

Abstract: In this paper, the experiments on phosphor-converted LEDs (pc-LEDs) with a correlated color temperature (CCT) of 8500K has been conducted with the scattering enhancement particles (SEPs) to achieve the higher color uniformity and emitted luminous flux of pc-LEDs. Moreover, this paper also introduced about choosing scattering enhancement particles (SEPs), including calcium carbonate (CaCO3) and titania (TiO2), and compared these particles' properties by adding them into the yellow Y3Al5O12:Ce 3+ phosphor compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To analyze the change in luminous efficiency of WLEDs using CaCO 3 and TiO 2 , the scattering computation applying Mie theory, and the transmitted light power calculation based on Lambert-Beer law, were utilized [25]:…”
Section: Computation and Discussionmentioning
confidence: 99%
“…To analyze the change in luminous efficiency of WLEDs using CaCO 3 and TiO 2 , the scattering computation applying Mie theory, and the transmitted light power calculation based on Lambert-Beer law, were utilized [25]:…”
Section: Computation and Discussionmentioning
confidence: 99%
“…Therefore, this research employs CaCO 3 and TiO 2 , which are frequently used in pc-LED, for the effectiveness in enhancement tests and then compares the results to pick out the most effective SEP. As the results of previous studies suggested, when giving SEPs the right particle size and concentration, they can enhance the lighting performance, therefore, the parameters that show how the SEPs influence the two lighting properties of pc-LED are also computed using Mie scattering theory and presented within the article. In this paper, the WLED package used for experiments has the correlated color temperature of 7000 K, not 8500 K as the previous one [16]. Moreover, the analysis of scattering property was presented and discussed in more detail to demonstrate the enhancement in color uniformity and lumen output.…”
Section: Introductionmentioning
confidence: 99%